Mechanical behavior of Zr-based bulk metallic glasses - Nowak, S.; Ochin, P.; Pasko, A.; Guerin, S.; Champion, Y. (Проблемы прочности, 2008)
Bulk metallic glasses have a very high corrosion resistance and mechanical strength. Bulk metallic glasses show elastic-perfectly plastic behavior with an extended region of elastic strain (≈ 2%). But at room temperature their macroscopic plasticity is weak even though a local plastic strain is observed in shear bands. A relaxation analysis allowed studying micro-mechanisms of plastic deformation and estimating the apparent activation volume (≈ 2000 Â³).